An Examination of Seventh Grade Students' Mistakes in Adjective Usage in Descriptive Writing at SMPN 1 Bandar - Sitanggang, Anita; Nababan, Irene Adryani (PT Inovasi Pratama Internasional, 2025)
This research was intended to find out the types of error in using adjective in writing descriptive text made by the seventh grade students of SMPN 1 BANDAR. This research was conducted at SMPN 1 BANDAR. This research was used quantitative approach and content analysis was employed as the research methodology. The total participants of this research were thirty-three students taken from eight grade of SMPN 1 BANDAR by using purposive sampling. In collecting the data, the researcher used a descriptive writing test. The errors were collected, identified and classified based on Dulay’s (1982) Surface Strategy Taxonomy (SST) which consisted of four types of error namely omission, addition, misformation, and misodering. The results showed that there were four types of errors made by students in descriptive writing, there were: 1) omission (25,80%), 2) addition (22,58%), 3) misformation (25,80) and 4) misordering (25,80%). This research indicated that misformation was the highest error made by students.